DSPACE Real-Time Implementation of MPPT-Based FLC Method - Abdullah M. Noman; Khaled E. Addoweesh; Hussein M. Mashaly (International Journal of Photoenergy)
Maximum power point trackers are so important in photovoltaic systems to improve their overall efficiency. This paper presents a photovoltaic system with maximum power point tracking facility. An intelligent fuzzy logic controller method is proposed in this paper to achieve the maximum power point tracking of PV modules. The system consists of a photovoltaic solar module connected to a DC-DC buck-boost converter. The system is modeled using MATLAB/SIMULINK. The system has been experienced under disturbance in the photovoltaic temperature and irradiation levels. The simulation results show that the proposed maximum power tracker tracks the maximum power accurately and successfully in all conditions tested. The MPPT system is then experimentally implemented. DSPACE is used in the implementation of the MPPT hardware setup for real-time control. Data acquisition and control system is implemented using dSPACE 1104 software and digital signal processor card. The simulation and practical results show that the proposed system tracked the maximum power accurately and successfully under all atmospheric conditions.